Crime and the composition of place: a micro-level longitudinal study of the (in)stability of street robbery hot spot locations and environments using Google Street View - Connealy, Nathan T. (Criminal justice studies, 2025)
This study simultaneously examines two foundational assumptions in crime and place research: that hot spots are locationally static and that their environmental compositions are dynamic over time. Using longitudinal Google Street View imagery and remote systematic social observation, we assessed the locational stability and environmental compositional change of Seattle’s most criminogenic street robbery hot spots. The results indicate that hot spot locations were generally static and time stable in the aggregate, but that the stability trajectories of individual hot spots tended to vary across yearly intervals. Relatedly, the environmental compositions of crime hot spots tended to be more dynamic and changed more frequently than control locations in their aggregate compositions, but individual features within hot spots varied in their presence and degree of dynamicity compared to the paired controls. The findings underscore the importance of using temporally sequenced environmental data in place-based research and highlight the need for individualized and situational hot spot crime reduction strategies. The uniqueness of individual crime hot spots may require case-by-case considerations in both research and practice.